The Impact of COVID Pandemic on Marketing Strategies - Almuntaser, Zinab (European Journal of Business and Strategic Management, 2025)
Purpose: In today’s competitive business environment, marketing strategies have become more critical than ever-especially considering the transformative impact of the COVID-19 pandemic. This study purpose is to investigate the long-term effects of the pandemic on marketing practices across businesses in the United Arab Emirates (UAE) and Saudi Arabia, with a focus on shifts in consumer behavior, strategic business adaptation and enduring changes in marketing planning. Methodology: The methodology used in this research is a qualitative research approach, utilizing stratifies interviews and surveys with marketing professionals across various sectors in the UAE and Saudi Arabia. This method allowed for in-depth insights into the evolving nature of marketing strategy in the region. Findings: The research reveals that the changes brought about by the pandemic are not temporary responses but have evolved into fundamental components of contemporary marketing strategies. Key finding indicates an accelerated embrace of digital transformation, a growing emphasis on localized targeting and agile marketing efforts. Unique Contribution to Theory, Practice and Policy: The study underscores the need for businesses to realign their marketing strategies to remain competitive in the post-pandemic landscape. This includes embedding digital tools into core operations, adopting localized and culturally sensitive marketing approaches and proactively meeting the elevated expectations of today’s consumers.